Not-for-Profit Accounting and Auditing in the Early Eighteenth Century: Some Archival Evidence - Swanson, G. A.; Gardner, John C. (The Accounting Review, 1988)
[Developments of accounting concepts and procedures in governmental, religious, and eleemosynary organizations have received scant attention in the literature. This study examines an extensive store of primary documents that chronicle the early development of the United Society for the Propagation of the Gospel in eighteenth century England. It concludes that the immediate impetus for auditing in the Society came from business practices rather than from government and that rudimentary managerial accounting procedures emerged in the Society as a result of internal needs for planning and control in much the same way they were emerging in businesses of the period.]